PENGETAHUAN DAN SIKAP PASIEN HIPERTENSI DENGAN TINDAKAN PENCEGAHAN SERANGAN STROKE DI RSUD TAMAN HUSADA BONTANG - Dyah Fartika Sari; Ratanto; Arsyawina Arsyawina (Jurnal Cakrawala Ilmiah, 2023)
A study reported in the last 20 years there has been an increase in stroke prevalence in several European countries, from 1.1 million/year in 2000 to 1.5 million/year in 2025. Preventive actions play a very important role in reducing the incidence of strokes. The success of stroke prevention is influenced by knowledge and attitude of hypertension patients. This study aims to analyse the correlation between knowledge and attitude with stroke attacks prevention of hypertension patients at Taman Husada Regional Hospital Bontang. Method: The research was conducted in cross-sectional. The subjects are 488 hypertension patients in Taman Husada Regional Hospital Bontang in 2022. Data was collected using questionnaires in google-form, which have 3 variables analysed; knowledge, attitude, and prevention of stroke. To calculate minimal sample for this study, the researcher used slovin equation, considering drop-outs, minimal numbers of sample obtained are 61 subjects. All the data are processed with statistic software and analysed with chi-square test. Results: Majority of respondents were mostly between 45-55 years old (66.1%), female (54.8%), high-school graduated (30.6%). Hypertensive patients have sufficient knowledge (51.6%) and have a good attitude towards stroke prevention (77.4%). There is a relation between knowledge and stroke prevention (p value 0.001) also there is a relationship between attitudes and stroke prevention (p value 0.001). Conclusion: Knowledge and attitude have significant relation with stroke attack prevention. Through this research, other studies hopefully can be arranged using a vaster population that produces a more detailed study about stroke prevention guidelines.